A Corticobasal Syndrome Variant of Familial Creutzfeldt-Jakob Disease with Stroke-Like Onset - Ján Necpál; Martin Stelzer; Silvia Koščová; Michal Patarák (Case Reports in Neurological Medicine)
Creutzfeldt-Jakob disease (CJD) is an untreatable rare human prion disease characterized by rapidly progressive dementia along with various neurological features, including myoclonus and sometimes other movement disorders. The clinical course is typically insidious and rapid, leading to an early death. In general, the most common form is sporadic CJD; however, Slovakia is typical for a high percentage of genetic cases. We present an unusual case report of a 65-year-old man with a sudden, stroke-like onset of motor aphasia with right-sided levodopa unresponsive parkinsonism, alien hand, and other characteristic features of corticobasal syndrome (CBS), with rapid deterioration and death on the 32nd day of the disease. Various neurodegenerative disorders are manifested with CBS as a clinical phenotype, including corticobasal degeneration (CBD), progressive supranuclear palsy, Alzheimer’s disease, and CJD. In our patient, mutation E200K and M129M polymorphism of the PRNP gene and typical immunohistochemical findings pointed to a diagnosis of CJD. The patient’s mother died of CJD many years ago. Several CBS-CJD cases were described, but the atypical stroke-like onset of CBS-CJD, an extremely rare presentation of CJD, makes our case unique worldwide.